Transcriptomic insights into early responses of the uterovaginal junction and vagina to avian influenza virus infection in turkey breeder hens - Kosonsiriluk, Sunantha; Santativongchai, Pitchaya; Reed, Kent M.; Studniski, Marissa M.; Wileman, Ben W.; Boukherroub, Kahina S. (Frontiers in Physiology, 2026)
IntroductionAvian influenza virus (AIV) infections, even with low-pathogenic strains (LPAIVs), can severely disrupt reproduction in turkey breeder hens. Although the vagina and uterovaginal junction (UVJ) are among the earliest mucosal sites exposed to pathogens, their early transcriptomic responses to LPAIV infection are uncharacterized.MethodsThis study investigated early transcriptomic changes in these tissues during both presymptomatic and symptomatic stages of LPAIV infection (n = 4/group/tissue). Flocks for sampling were classified as presymptomatic or symptomatic based on drinker swab LPAIV testing and egg production records. Presymptomatic group consisted of infected hens from LPAIV-negative barns. These flocks had stable egg production at the time of collection but with a subsequent egg drop. The symptomatic group included infected hens from LPAIV-positive barns with reduced egg production and sampled 2–3 days post-detection.ResultsPrincipal component analysis of high-throughput RNA-seq data, identified symptomatic status as the primary driver of gene expression variance, followed by tissue origin. In the UVJ, 4,683 genes were differentially expressed (adjusted P-value < 0.05; Log2fold change ≥ 1.5), with symptomatic birds showing upregulation of genes involved in cellular remodeling and transport, and downregulation of those related to protein synthesis and metabolic pathways. Gene Set Enrichment Analysis (GSEA) confirmed significant upregulation of the insulin signaling pathway and downregulation of cytokine-cytokine receptor interaction, ribosome, and peroxisome proliferator-activated receptor signaling, indicating metabolic disruption and immune system alteration. The vagina presented a distinct transcriptomic profile, with 701 differentially expressed genes identified between the symptomatic vs. presymptomatic groups. In the symptomatic vagina, upregulated pathways were linked to gene regulation and biosynthesis, while downregulated pathways involved protein synthesis, metabolism, energy production, and vascular development.DiscussionThese findings reveal early, tissue-specific molecular vulnerabilities to LPAIV. The UVJ shows disruptions in cellular maintenance and metabolism, potentially impairing fertility, while the vaginal response suggests heightened early immune activation but later compromised barrier integrity. This study offers potential mechanistic insights into LPAIV-induced reproductive pathologies, providing a foundation for targeted strategies to reduce viral impact on flock health and maintain production efficiency.